Use of Statins for Dyslipidemia in the Pediatric Population - Eiland, Lea S. (Pediatric Pharmacy Advocacy Group, 2010)
Childhood dyslipidemia is on the rise and increasingly being recognized as an important risk factor for adult cardiovascular disease. Due to a heightened awareness surrounding this problem, the American Academy of Pediatrics published a clinical report concerning prevention, screening, diagnosis, and treatment of dyslipidemia in children. Of concern among practitioners is when to initiate pharmacologic therapy and which medications are safe and appropriate in children. The report addresses this concern by suggesting that pharmacologic management begin only in pediatric patients with substantially elevated LDL levels. Since statins are the drugs of choice among adult patients with elevated LDL levels, it would be appropriate to evaluate their outcome in pediatric patients. To evaluate the efficacy and safety of statins for the treatment of pediatric dyslipidemia, a comprehensive search was performed of the MEDLINE database and International Pharmaceutical Abstracts as well as references from additional review articles. The manufacturer was contacted for data regarding a newly approved statin. Fourteen trials were identified, eight of which were randomized, controlled trials involving greater than 50 patients with primary or familial hypercholesterolemia. Overall, the studies showed that statins are effective at lowering LDL levels (reduction from baseline: 17% to 50%) and are fairly well tolerated, with headache, gastrointestinal distress, and myalgia being the most common adverse effects. Statins were found to be an efficacious option for the management of familial hypercholesterolemia of childhood. However, concerns regarding long term safety and efficacy have not been established, and data in patients with secondary lipid disorders is lacking.